THE NECESSITY OF BILINGUAL APPROACH IMPLEMENTATION AT HIGHER EDUCATIONAL ESTABLISHMENTS - Martovytska, Nataliia; Lokhvytska, Liubov (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article highlights the results of the bilingual approach implementation to the process of preparing students for their professional competencies in the context of higher education system reformation. The topicality of the study is caused by the fact that the entry of Ukrainian society into the European space imposes appropriate requirements for the new generation specialists’ training. The purpose of the study was to substantiate theoretically and verify experimentally the implementation of a bilingual approach to learning a foreign language in the process of teaching some professional disciplines in order to improve the professional training of students of non-linguistic specialties. To achieve this goal, we used the following methods: to collect empirical survey data (student questionnaires and interviews with teachers), a statement experiment to find out the real state of the problem under investigation, a search experiment to implement the bilingual approach in the study of foreign language and its control.The experiment was participated by students of the 1st and 2nd years of study of non-linguistic specialties students at higher educational institutions during four terms, the study was carried out in three stages. At the first stage the level of preparation of the first-year students of non-linguistic specialties was studied. The results demonstrated that more than half of the respondents had difficulties in mastering the material. At the second stage of the study, a search experiment was conducted using a bilingual approach. In the course of the effectiveness approach checking, it was recorded that students demonstrated a sufficient level of foreign language proficiency due to the systematic use of the bilingual approach while studying basic disciplines.